Generalized Convolution Roots of Positive Definite Kernels on Complex Spheres - Barbosa, V.S.; Menegatto, V.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
Convolution is an important tool in the construction of positive definite kernels on a manifold. This contribution provides conditions on an L²-positive definite and zonal kernel on the unit sphere of Cq in order that the kernel can be recovered as a generalized convolution root of an equally positive definite and zonal kernel.